Three-dimensional (3D) printing and its applications for aortic diseases - Hangge, Patrick; Pershad, Yash; Witting, Avery A.; Albadawi, Hassan; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Abstract: Three-dimensional (3D) printing is a process which generates prototypes from virtual objects in computer-aided design (CAD) software. Since 3D printing enables the creation of customized objects, it is a rapidly expanding field in an age of personalized medicine. We discuss the use of 3D printing in surgical planning, training, and creation of devices for the treatment of aortic diseases. 3D printing can provide operators with a hands-on model to interact with complex anatomy, enable prototyping of devices for implantation based upon anatomy, or even provide pre-procedural simulation. Potential exists to expand upon current uses of 3D printing to create personalized implantable devices such as grafts. Future studies should aim to demonstrate the impact of 3D printing on outcomes to make this technology more accessible to patients with complex aortic diseases.